Preliminary analysis of an agent-based model for a tick-borne disease - Holly Gaff (Mathematical Biosciences and Engineering)
Ticks have a unique life history including a distinct set of life stages and asingle blood meal per life stage. This makes tick-host interactions more complexfrom a mathematical perspective. In addition, any model of these interactionsmust involve a significant degree of stochasticity on the individual tick level.In an attempt to quantify these relationships, I have developed an individual-basedmodel of the interactions between ticks and their hosts as well as the transmissionof tick-borne disease between the two populations. The results from this model arecompared with those from previously published differential equation based populationmodels. The findings show that the agent-based model produces significantly lower prevalenceof disease in both the ticks and their hosts than what is predicted by a similardifferential equation model.